Mitofusin 1 and 2 overexpression reduces AβO-mediated ER stress and apoptosis in N2a APPswe cells: Role of mitofusin in AβO-mediated ER stress - Kam, Min Kyoung; Jung, Su-Min; Lee, Ga Eun; Lee, Sung Woo; Lee, Hong Jun; Park, Young-Ho; Lee, Dong-Seok (Cellular and Molecular Biology, 2024)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, and amyloid beta oligomers (AβO), which are pathological markers of AD, are known to be highly toxic. AβO increase mitochondrial dysfunction, which is accompanied by a decrease in mitochondrial fusion. Although mitofusin (Mfn) 1 and Mfn2 are mitochondrial fusion proteins, Mfn2 is known to regulate endoplasmic reticulum (ER) function, as it is located in the ER. Several studies have shown that AβO exacerbates ER stress, however, the exact mechanism requires further elucidation. In this study, we used mouse neuroblastoma cells stably overexpressing the amyloid precursor protein (APP) with the Swedish mutation (N2a APPswe cells) to investigate the role of Mfn in ER stress. Our results revealed that amyloid beta (Aβ) caused cellular toxicity in N2a APPswe cells, upregulated ER stress-related proteins, and promoted ER expansion. The AβO-mediated ER stress was reduced when Mfn1 and Mfn2 were overexpressed. Moreover, Mfn1 and Mfn2 overexpressed resulted in reduced apoptosis of N2a APPswe cells. In conclusion, our results indicate that both Mfn1 and Mfn2 reduce ER stress and apoptosis. Our data provide a foundation for future studies on the roles of Mfn1 and Mfn2 in the molecular mechanisms underlying AβO-mediated ER stress and the pathogenesis of AD.